2014
DOI: 10.1007/s11149-013-9237-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of regulation and competition on the adoption of fiber-based broadband services: recent evidence from the European union member states

Abstract: Although fibre-deployment of next generation access (NGA) broadband networks is considered as a decisive development for any information-based society, investment activities and especially the adoption of fiber-based broadband services take place only very gradually in most countries. This work identifies the most important determinants of NGA broadband adoption, using most recent panel data from the European Union member states (EU27) for the years from 2004 to 2012.The results show that stricter previous bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 39 publications
(28 reference statements)
1
31
1
Order By: Relevance
“…8 These findings challenge the viability of the existing regulatory framework. Currently it targets the effectiveness of wholesale broadband access regulation imposed on the incumbent's first generation network which, however, might impede the rollout of future ultra-fast networks (Briglauer, 2014;European Parliamentary Research Service, 2015). The second strand analyzes broadband retail prices and shows that data restrictions lead to lower prices and that increased quality, in terms of increased download-speed, drives prices upwards (Wallsten and Riso, 2010).…”
Section: Ftth Council Europe (2016) Der Ftth Markt In Europamentioning
confidence: 99%
See 3 more Smart Citations
“…8 These findings challenge the viability of the existing regulatory framework. Currently it targets the effectiveness of wholesale broadband access regulation imposed on the incumbent's first generation network which, however, might impede the rollout of future ultra-fast networks (Briglauer, 2014;European Parliamentary Research Service, 2015). The second strand analyzes broadband retail prices and shows that data restrictions lead to lower prices and that increased quality, in terms of increased download-speed, drives prices upwards (Wallsten and Riso, 2010).…”
Section: Ftth Council Europe (2016) Der Ftth Markt In Europamentioning
confidence: 99%
“…Ward and Woroch, 2010; Barth and Heimeshoff, 2014; Grzybowski and Verboven, 2016; Lange and Saric, 2016) and it has been shown that FMS even affects the broadband market. According to Briglauer (2014), FMS and NGA adoption follow an inverted U-shaped relationship. On the one hand, competition in the legacy market incentivizes investments to escape the competition and gain a firm position in the new frontier market, leading to a positive relationship ("escape competition effect").…”
Section: Independent Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…There are very few papers that deal with NGN demand adoption (point (ii)). Wallsten and Hausladen (2009) Briglauer (2014) has investigated the determinants of NGN adoption for EU27 member states from 2004 to 2013. The author has found that the more effective the previous broadband access regulation was, the more negative the impact on adoption.…”
Section: Literature Reviewmentioning
confidence: 99%